2018
DOI: 10.1097/brs.0000000000002450
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Vertebral Endplate Defects on Magnetic Resonance Images

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 46 publications
5
31
5
Order By: Relevance
“…An analysis of the Pfirrmann grading revealed the prevalence of grades in the following percentages: I (0.75%), II (14.25%) III (37.5%), IV (36.5%), and Grade V discs (11%). These research discoveries suggest that our patients had more serious degeneration of lumbar discs in comparison with those reported in other studies (23)(24)(25). For all patients, we summarized all grades and correlated them with ODI and VAS test revealed a significant correlation in the Pfirrmann grades, VAS (p = 0.16), and ODI (p = 0.24).…”
Section: Discussionsupporting
confidence: 71%
“…An analysis of the Pfirrmann grading revealed the prevalence of grades in the following percentages: I (0.75%), II (14.25%) III (37.5%), IV (36.5%), and Grade V discs (11%). These research discoveries suggest that our patients had more serious degeneration of lumbar discs in comparison with those reported in other studies (23)(24)(25). For all patients, we summarized all grades and correlated them with ODI and VAS test revealed a significant correlation in the Pfirrmann grades, VAS (p = 0.16), and ODI (p = 0.24).…”
Section: Discussionsupporting
confidence: 71%
“…Earlier studies have shown, that endplate changes and DDD are related. [20,8] In the present study, no relevant increase of DDD grade was seen during follow up.…”
Section: Discussioncontrasting
confidence: 57%
“…Earlier studies have shown, that endplate changes and DDD are related. [21,8] In the present study, no relevant increase of DDD grade was seen during follow up.…”
Section: Discussioncontrasting
confidence: 57%